(untitled) (Damascus University Journal of arts and humanities sciences, 2024)
Random solid waste dumps pose an environmental threat. In this research, we seek to study the environmental impacts of the Sweida (Kanaker) waste dump, by assessing the quality of groundwater in the surrounding wells by conducting analyzes of water samples taken from six artesian wells and determining their pollution indicators. The content was determined The total concentrations of some heavy elements. The samples were collected from the waste dumping site in the landfill and at time intervals from the years 2021 and 2022 AD, at a rate of one sample for the months. The first sample was in December of 2021 AD, and the rest of the samples were in 2022 AD. The second sample was in the month of March, and the third sample was in In June, and the fourth sample in November, it was taken into account that the sample should be collected during wet and dry periods. A survey of the opinions of local residents was also conducted to determine the possible effects of pollution on them. However, the results of the analysis of well water samples showed that there is no leaching of leachate from the mass of waste in the landfill into the groundwater, as it is within the permissible limits according to the standard specifications for Syrian drinking water. The results of the soil analysis indicated the presence of a number of Coliform cologne bacteria and the presence of Escherichia coli bacteria. The research relied mainly on the descriptive analytical approach and the inductive analytical approach to analyze the existing relationships between the Sweida (Kanaker) landfill site and the quality of water and soil. The research also relied on the deductive approach to present the conclusions and results of the research. .